2020
DOI: 10.25000/acem.650341
|View full text |Cite
|
Sign up to set email alerts
|

Evre II-IV rektum kanserinde metabolik destekli kemoterapinin ketojenik diyet, hipertermi ve hiperbarik oksijen tedavisi ile kombinasyonunun ön sonuçları

Abstract: Aim: Systemic chemotherapy is a part of multi-modality treatment in patients with stage II-IV rectal cancer. In particular, patients not eligible for curative resection at the time of diagnosis require more efficient approaches to improve outcomes. Metabolically supported chemotherapy (MSCT) is a novel approach targeting dysregulated energy mechanism of the tumor cell. This study aimed to examine the efficacy of MSCT combined with ketogenic diet, hyperthermia and hyperbaric oxygen therapy (HBOT) in patients wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 50 publications
0
8
0
Order By: Relevance
“…Previous studies with MSCT regimens that have also reported encouraging findings in patients with various types of malignancies include five retrospective case series [ 6 , 9 - 12 ]​​​​​​ and two case reports [ 7 - 8 ]. A recent study evaluated the efficacy and tolerability of weekly carboplatin/paclitaxel combination treatment administered in a metabolically supported manner in patients with metastatic non-small cell lung carcinoma (NSCLC), reporting mean OS of 42.9 months compared to survival times with standard conventional treatment ranging from 6.3 to 11.3 months [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Previous studies with MSCT regimens that have also reported encouraging findings in patients with various types of malignancies include five retrospective case series [ 6 , 9 - 12 ]​​​​​​ and two case reports [ 7 - 8 ]. A recent study evaluated the efficacy and tolerability of weekly carboplatin/paclitaxel combination treatment administered in a metabolically supported manner in patients with metastatic non-small cell lung carcinoma (NSCLC), reporting mean OS of 42.9 months compared to survival times with standard conventional treatment ranging from 6.3 to 11.3 months [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…Premedication consisted of 45.5 mg of pheniramine maleate, 0.25 mg of palonosetron hydrochloride, and regular insulin (Humulin® R) in doses ranging between 5 and 10 IU to attain mild hypoglycemia, defined as blood glucose levels of approximately 50 - 60 mg/dL (in accordance with MSCT protocols) [ 6 - 12 ]​​​​. The patient received 17 treatment sessions in each session after 14-hour fasting.…”
Section: Case Presentationmentioning
confidence: 99%
See 3 more Smart Citations